Tokyo 2020: a sociodemographic and psychosocial characterization of the Portuguese paralympic team - Mira, T.; Monteiro, D.; Costa, A. M.; Morouço, P.; Matos, R.; Antunes, R. (healthcare, 2021)
The importance of practicing sports and its impact on the quality of life of people with disabilities is fundamental. Characterizing subjective well-being, resilience, and social influence in the practice of adapted sports, namely in those who participate in elite sport in Portugal, is truly important to support a set of initiatives to promote higher levels of practice. Thus, this study describes the Portuguese delegation at the Tokyo 2020 Paralympic Games through sociodemographic and psychosocial (positive and negative affect, life satisfaction, resilience, and social support) variables. The study involved 31 of the 33 athletes of the Portuguese Paralympic team aged between 15 and 58 years (34.45 ± 11.7 years), with 21 men and 10 women. Individual-level sociodemographic data gave us a clear insight into the reality of adapted sport in Portugal. The high values of life satisfaction, high positive affect and low negative affect, as well as high levels of resilience and social support seem to be important variables for these athletes. The data from the present study highlighted the importance of understanding the characteristics of Paralympic athletes, in order to better understand the reality of Paralympic sport in Portugal.